Perspektif Buddhis Mengenai Pendekatan Perilaku Realita - Diah Arum Puji Astuti; Kabri Kabri; Julia Surya (Journal on Education, 2023)
This journal explores the Buddhist perspective regarding the behavioral reality approach as a concept that includes spiritual, philosophical and psychological aspects. This approach is based on basic Buddhist concepts such as freedom from suffering (dukkha) and a deep understanding of attachment (tanha) to reality. This journal outlines key Buddhist concepts related to the behavioral reality approach, such as mindfulness (awareness), impermanence (anicca), and concern for suffering (karuna). In addition, this journal discusses how Buddhist understanding of reality can shape patterns of behavior and responses to the surrounding environment. Through a qualitative approach, this research involves analysis of classical Buddhist texts and interviews with Buddhist practitioners who have applied the reality-behavior approach in everyday life. The results suggest that Buddhist understanding of reality can provide a basis for the development of behavioral policies and therapeutic practices that include spiritual and psychological aspects. This research provides in-depth insight into how a Buddhist perspective can contribute to the understanding and treatment of behavioral realities in contemporary contexts.